Achievements And Problems in Further Development of The Digital Economy in UzbekistanScientific Considerations (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
In the 21st century, digital technologies and innovative business models cover all spheres of society's life and improve structural changes in the quality of economic activity. As a result, the digital economy, characterized by the active use of digital technologies and the circulation of unique digital information, is passing its judgment as a separate mechanism of the traditional economy. Today, when science and information-communication and digital technologies are developing rapidly, digital technologies are used in the developed countries of the world in public and social management, economy, industry, social protection, education, medicine, employment, agriculture, defense, security, tourism and other fields. and the widespread use of artificial intelligence capabilities is being taken as a model. The level of development of the digital economy is directly related to the competitiveness of each country, requiring countries to pay special attention to its development. Digitization is applied to social processes, and the advanced achievements of the information society depend on it. Uzbekistan does not take the leading place in the world in terms of the level of development of the digital economy, but it is increasing its position in this field year by year.